PEMBERDAYAAN MASYARAKAT DESA : IMPLEMENTASI EKONOMI HIJAU SEBAGAI BENTUK OPTIMALISASI PRODUK HASIL HUTAN DI DESA TETEBATU, LOMBOK TIMUR - Satriawan, Nurholid; Afifah, Adzra; Syamsuhaidi, Syamsuhaidi; Aeni, Nurul; Haryono, Iffatul Hanifah; Parwati, Ni Kadek Tika; Sufi, Nilmayana; Hafizin, Lalu Khairul; Junianti, Baiq Riza; Suryani, Wida (Jurnal Wicara, 2024)
Tetebatu Village has abundant biodiversity and natural potential, which needs to be protected to maintain its sustainability. The green economy concept is a relevant approach to protecting natural wealth in this village. The aim of this activity is to actualize the green economy through various initiatives that have an impact on economic, social, and environmental aspect. One way of implementing a green economy in Tetebatu Village is through the production of Trigona Honey. This activity method certainly examines the problem in Tetebatu Village, namely that the implementation of the green economy has not been optimal due to inadequate facilities and infrastructure, especially in the production of Trigona Honey over the last two years, so a Forest Product Optimazation program is needed. The result of student dedication in this case show be a positive impact. Before this program, Trigona Bee had difficulty finding plants around the cultivation location, indicating that there were not yet optimal. This program contributes by planting coffe seedlings around cultivations locations, which is expected to increase Trigona Bee production. Apart from that, the addition of Trigona Bee stock was also carried out to further optimize production. Thisefforts aims to increase result and effectiveness in sustainable Trigona Honey production. The conclusion of this agenda is the creation of an optimal and comprehensive green economy in Tetebatu Village